NEW CONCEPTS AND CHALLENGES FOR TEACHER EDUCATION FOR TVET – WORK INTEGRATED LEARNING THROUGH THE CAREER CHANGE PROGRAM - Moore, Rod; Pitard, Jayne; Greenfield, Rosie (UPI Press, 2012)
This paper examines the effectiveness and outcomes of an innovative teacher education for ‘beginning’ teachers with full careers in other professions and industries. Data were gathered over 3 years to study the experience of these teachers who undertake their initial teacher education and enter the profession simultaneously. This work is a benchmark practice of Victoria University (VU) commitment to enhancing educational access, participation and success for young people in the region. VU has formed a partnership with secondary schools delivering VET and the Department of Education and Early Childhood Development to address teacher shortages in secondary schools. The Career Change Program (CCP) has been developed to address this shortage by attracting qualified professionals with industry experience to teach in teacher-short-supplied subject areas. Praxis Inquiry (PI) model of teacher education is developed and applied by focusing on teacher learning in school settings. The program aims to set in place practices and procedures in partnership with key stakeholders that provide a framework for sustainable recruitment, selection and education of Career Change Teachers in Vocational Education. This framework will develop an international best practice of teacher education constructed as a partnership between schools, communities and university.